Comparison between conventional radiograph and 3D volumetric radiograph for determining the morphology and morphometry of mental foramen - Rakashree Chakraborty; Sourav Sen; Arati Panchbhai; Rahul R Bhowate; Aditya Dupare (Wolters Kluwer Medknow Publications, 2019)
Objective: Mental foramen is a vital anatomical structure in human mandible as they are important for dental surgeons for extraction, implant placement, osteotomy procedures, anesthetists in nerve block, and surgical procedures to avoid injury to neurovascular bundle in mental foramen area. The aim of this study was to compare the position, shape, size, and distinctness of mental foramen using orthopantomogram (OPG) and digitalized volumetric tomography (DVT). Materials and Method: This study was conducted on 25 individuals for both the genders. Position, shape, size, and distinctness of mental foramen were compared using OPG and DVT and were evaluated by Expert three-dimensional (3D) software in DVT and Annotation software in OPG. Results: Mental foramen was found to be on the vicinity of the second premolar region with respect to apices of premolars and molars and was more common in the middle third region of the jaw bone with respect to superoinferior cortex of the mandible in vertical plane. There was no significant difference in the position of the mental foramen using OPG and DVT. The commonest shape of mental foramen was found to be oval and was better defined in DVT. The size of the mental foramen was observed to be 0.49 ± 0.05 and 0.51 ± 0.06 cm in OPG and DVT, respectively, and more distinctly visible in DVT. There was no significant difference in the position, shape, size, and distinctness of the mental foramen among genders. Conclusion: Conventional radiography can be initially done for the position of the mental foramen but the details must be confirmed using 3D volumetric radiography to avoid any kind of procedural complications.